Differences Flow OfDetantion In Immigration Office Of SoekarnoHatta And The Immigration Detention House Of Jakarta - Muhammad Anugerah Ariyanto; Rinaldi Rachmansyah Putra (IHSA Institute, 2021)
Migration Violations committed by foreign nationals must be subject on Immigration Administrative Actions (TAK). Foreigners who are subject to TAK are placed in the Immigration Detention Room located at The Immigration Office such as The Immigration Office of SoekarnoHatta, while in the Detention Room, foreign are attempted to be deported but if 30 days pass, they will be transferred to Rudenim for detention. This research method uses normative-empirical methods in conducting observations to clarify what function of each both. The results of this research are the differences in the flow of detention between The SoekarnoHatta detention room and Rudenim of Jakarta. Suggestion that can be given from this research should be to optimize the detention room facilities at The Immigration Office.